Analisis Evaluasi Merek Sunscreen Glad2glow Di Kalangan Mahasiswa Manajemen - Sika Noviani; Apriyani; Syamsul Hidayat (Student Research Journal, 2024)
Based on data released in 2023, the human need to use sunscreen is very important for every human being. Research results show that sunscreen is very important for teenage skin, because at the age of teenagers, facial skin has begun to be exposed to sunlight due to high levels of outdoor activity. However, choosing It is very important to do good sunscreen so that the skin does not become more problematic due to the chemicals contained in sunscreen products. Therefore, this research aims to find out how important it is to use sunscreen among semester 1 3 5 students of Bina Bangsa University. Based on that introduction, theoretical studies and data processing as well as discussions that have been carried out in the previous chapter. The main goal of this technique is to extract relevant information, identify patterns or trends, and gain a better understanding of the phenomena represented by the data. This quantitative research data analysis technique uses the help of Excel and SPSS. sunscreen products, that not using sunscreen can cause many dangers to skin health, such as premature aging, the appearance of blackheads and skin damage and cancer and can trigger the appearance of new lesions in several types of skin diseases.